Electron Dynamics in Magnetosheath Mirror‐Mode Structures. Issue 7 (27th July 2018) - Yao, S. T.; Shi, Q. Q.; Liu, J.; Yao, Z. H.; Guo, R. L.; Ahmadi, N.; Degeling, A. W.; Zong, Q. G.; Wang, X. G.; Tian, A. M.; Russell, C. T.; Fu, H. S.; et al.
Abstract: Mirror‐mode structures are widely observed in space plasma environments. Although plasma features within the structures have been extensively investigated in theoretical models and numerical simulations, relatively few observational studies have been made, due to a lack of high‐cadence measurements of particle distributions in previous space missions. In this work, electron dynamics associated with mirror‐mode structures are studied based on Magnetospheric Multiscale observations of electron pitch angle distributions. We define mirror‐mode peaks/troughs as the region where the magnetic field strength is greater/smaller than the mean field. The observations show that most electrons are trapped inside the mirror‐mode troughs and display a donut‐like pitch angle distribution configuration. Besides the trapped electrons in mirror‐mode troughs, we find that electrons are also trapped between ambient mirror‐mode peaks and coexisting untrapped electrons within the mirror‐mode structure. Analysis shows that the observed donut‐like electron distributions are the result of betatron cooling and the spatial dependence of electron pitch angles within the structure. Key Points: Electron PADs of magnetosheath mirror modes are observed by MMS The PADs display a characteristic donut‐like configuration Betatron cooling and spatial dependence of electron pitch angle are able to produce such a distribution